United Kingdom and United States healthcare providers' recommendations of abstinence versus controlled drinking - Cox, W; Rosenberg, H; Hodgins, C; Macartney, J; Maurer, K (Oxford University Press, 2004)
Aim: To assess whether selected characteristics of problem drinkers influence treatment goal recommendations — abstinence or controlled drinking — by healthcare providers in the UK and the US. Methods: Sixteen case-histories, composed with varying information regarding the clients' level of problem severity, degree of social support and sex, were read by 41 UK and 31 US healthcare providers, who then gave a recommendation of controlled drinking versus abstinence for each case on a seven-point Likert scale. Results: Overall, abstinence was recommended more strongly for higher-severity problem drinkers, those with higher social support (an unpredicted finding), and for female clients. Controlled drinking was more often recommended in the UK than in the US. However, the degree to which drinkers' problem severity, social support and sex each affected respondents' ratings depended on the level of one or more of the other variables and the country of the respondents. Conclusion: The degree to which healthcare providers recommend abstinence or controlled drinking as an outcome goal for problem drinkers varies according to both client characteristics and the country in which they work.